PELATIHAN DIGITAL DAN PEMANFAATAN TEKNOLOGI INFORMASI DALAM PEMBELAJARAN DI SEKOLAH DASAR DI KOTA KUPANG - Diana Fallo; Maria Sogen (Merwinspy Publisher, 2026)
This community service activity aimed to improve teachers’ digital competencies and optimize the use of Information and Communication Technology (ICT) in elementary school learning in Kupang City, East Nusa Tenggara. The program was implemented in four elementary schools using a Participatory Action Research (PAR) approach through several stages, namely problem identification, preparation of training materials, workshop-based training, mentoring, monitoring, and program evaluation. The training focused on the use of digital learning applications such as Quizizz, Wordwall, Canva, YouTube, and ChatGPT to support interactive and adaptive learning. The results showed a significant improvement in teachers’ digital competencies. Quantitative evaluation indicated that the average participant competency score increased from 56% before the program to 84% after the training, with an improvement rate of 28%. In addition, 75% of participants were able to independently implement digital learning media in classroom activities, while 87% of participants expressed positive satisfaction with the program. Teachers also demonstrated increased confidence in using technology to design interactive learning activities and support students with diverse learning needs. Despite these positive outcomes, several challenges were identified, including limited internet access, unequal availability of digital devices, and the need for continuous mentoring. Overall, the program contributed positively to strengthening digital literacy, improving the quality of technology-based learning, and encouraging the development of more inclusive digital learning practices in elementary schools in Kupang City